THE RELATION OF A COST ACCOUNTANT TO THE NRA CODES. - Taggart, Herbert F. (The Accounting Review, 1934)
Abstract When the National Industrial Recovery Act (NIRA) gave the U.S. President power to impose requirements for the making of reports and the keeping of accounts, when it banned unfair competitive practices and indicated that destructive price cutting was one of them, and when the codes of fair competition almost from the first provided for uniform systems of accounting for industries and specified that selling products or services below cost was destructive price cutting, accountants began to sit up and take notice. The NIRA does not, of course, constitute the first time that accounting has been given recognition as a means of facilitating the relations of government to private industry. One needs only to point to the uniform accounting systems devised by the Interstate Commerce Commission and the several state utilities commissions for railroads and utilities. The several Revenue Acts enacted since 1913 have in effect required all taxpayers and potential taxpayers to keep such records as would make possible an accurate determination of the liability for income taxes.